Numerical Study on the Thermal Performance of Trombe Wall for Passive Solar Building in Semiarid Climate - Maher Dhahri; Nima Khalilpoor; Hana Aouinet; Alibek Issakhov; Habib Sammouda; Sampath Emani (International Journal of Photoenergy)
The largest amount of energy in buildings is consumed to provide heating, cooling, and ventilation. Therefore, a practical solution such as using renewable energy sources can be considered to reduce energy costs and pollutants. In addition, architecture principles must be varied to utilize passive solar energy and also to reduce energy losses. In this research, a numerical study is presented to investigate the thermal behavior of TW-FR (Trombe wall placed in a fenestrated room) in the semiarid region of Tunisia. Computational fluid dynamic (CFD) simulation of fluid flow and heat transfer shows good agreement with published data in literature. The thermal comfort level was calculated according to ASHRAE (55-2013). The results show that (i) the normal Trombe wall cannot assure a satisfactory comfort level even in summer conditions and a higher vertical temperature gradient can take a value of 15°C, and the Trombe wall is shown to be more efficient in heating mode in the studied semi-arid region compared to cooling; (ii) the operative temperature for the coldest winter is between 17.85 and 19.85°C. The air temperature gradient in the comfort ranges between the head and feet is 2.3°C; and (iii) the Trombe wall is an excellent solution for Sousse city weather; it is suggested that the passive system (TW-FR) will be examined for a whole year to have a precise evaluation of its efficiency.